Pengaruh Media Promosi Instagram Terhadap Kepuasan Konsumen pada Toko Dessert Box Vanila Sweet - Shafira Ayu Setyawati Jamalong; Yeni Yulianti; Mutiara Dahlia (Ridwan Institute, 2022)
This study aims to analyze the effect of Instagram promotion media on consumer satisfaction at the Vanila Sweet dessert box shop. Consumer satisfaction is the level of consumer feelings after making a comparison between the goods/services received and what is expected. The independent variable in this study is Instagram promotion media and the dependent variable is dessert box consumer satisfaction. This research was conducted at a dessert box shop, Vanila Sweet, which is located in Bogor City from March 2021 to May 2022. The method used in this research is a survey method with quantitative research and descriptive quantitative approach. The sample of this study involved 64 respondents and used purposive sampling method. This study shows the results of the correlation test for the correlation value of the Instagram promotional media variable on consumer satisfaction is 0.403. The correlation of these two variables can be categorized as moderate. Based on the calculation of the coefficient of determination of 0.1624 or 16.24%. That is, in this study the distribution of data on the promotional media variable, namely Instagram, can predict customer satisfaction by 16.24%. The regression coefficient on the Instagram media promotion variable is 0.912, thus every increase in the score of the Instagram promotion value carried out by the Vanila Sweet dessert box shop will increase consumer satisfaction by 0.912 score at a constant 54.500.